2016
DOI: 10.1108/aeat-06-2015-0154
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quasi static indentation and dynamic loads of glass and carbon fibre aluminium laminates

Abstract: Purpose -The purpose of this paper was to compare the response of selected hybrid Fibre Metal Laminates (FMLs) in the form of glass and carbon fibre aluminium laminates to dynamic and static loads compared together. Design/methodology/approach -The subject of examination was FMLs (Al/CFRP and Al/GFRP). The samples were subjected to low-velocity impact and quasi-static indentation. The response of laminates to the both types of loads was evaluated by comparison of force -displacement diagrams including the valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…6,10,25,27 The course of f–t curves as well as the value of P i and P m may constitute a basis for assessment and comparison of the composite material and FMLs resistance to low-velocity impact. 8,12,24,28–31…”
Section: Resultsmentioning
confidence: 99%
“…6,10,25,27 The course of f–t curves as well as the value of P i and P m may constitute a basis for assessment and comparison of the composite material and FMLs resistance to low-velocity impact. 8,12,24,28–31…”
Section: Resultsmentioning
confidence: 99%
“…They analyzed the effect of various mechanical and chemical surface preparation methods (including alkaline process and engraving with sulfochochromic solution) on bending behavior using a three-point bending test. Jakubczak and Bienias 35 considered the quasi-static indentation of glass fiber-reinforced aluminum FML plates against static and dynamic loads. The results of their study presented that the level of degradation observed in carbon FMLs exposed to dynamic loads is significantly smaller than the indentations created against quasi-static loads.…”
Section: Introductionmentioning
confidence: 99%
“…The low-velocity impact behavior of FMLs was examined by Jakubczak et al (2014). Jakubczak and Bienias (2016) reported the experimental results on FMLs subjected to low-velocity impact and quasi-static loading. Most of the studies mentioned above are focused on the impact behavior of FMLs.…”
Section: Introductionmentioning
confidence: 99%